Harmoni Antara Wahyu Dan Logika: Implikasi Nilai Al-Qur'an Dalam Pendidikan Sains - Faiz Rahmawati (PEDAGOGIA : JURNAL KEGURUAN DAN PENDIDIKAN, 2024)
This research aims to examine the integration of Qur'anic values in science education and its impact on students' understanding of the relationship between revelation and logic in science. Along with the development of education that demands the merging of scientific knowledge and ethics, this research tries to explore how religious values can enrich science learning in Islamic-based schools. This type of research is descriptive qualitative research with a case study approach. The main data sources come from in-depth interviews with teachers and students, as well as observation of the Qur'an-based science learning process in several schools. This study aims to find out how Qur'anic values are applied in science learning and how they affect the development of students' moral attitudes and scientific understanding. The results show that the integration of revelation in science education has a positive impact on students' critical and reflective attitude towards science, while strengthening their moral understanding. Despite the challenges in linking scientific concepts with religious values, the application of Qur'anic values in science education proved to make an important contribution in shaping a more holistic student character, with a balance between scientific knowledge and moral ethics.